2004
DOI: 10.1016/j.concog.2003.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Action, arousal, and subjective time

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent repository link: AbstractSaccadic chronostasis refers to the subjective temporal lengthening of the first visual stimulus perceived after an eye movement. It has been quantified using a duration discrimination task. Most models of human duration discrimination hypothesise an internal clock. These models could explain chronostasis as a transient increase in internal clock speed du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 39 publications
4
30
1
Order By: Relevance
“…The post-saccadic image may be being antedated, to stitch up the temporal gap induced by saccadic suppression and masking [24,[26][27][28][29]. An active mechanism is implied because chronostasis emerges over and above any time dilation induced in passive control conditions, which simulate the visual effects of a saccade.…”
Section: Time Perception In the Context Of Actionmentioning
confidence: 99%
“…The post-saccadic image may be being antedated, to stitch up the temporal gap induced by saccadic suppression and masking [24,[26][27][28][29]. An active mechanism is implied because chronostasis emerges over and above any time dilation induced in passive control conditions, which simulate the visual effects of a saccade.…”
Section: Time Perception In the Context Of Actionmentioning
confidence: 99%
“…If action-linked changes motor cor in temporal perception were attributed to an adjustment in the rate of an internal clock, the weigh then the magnitude of this effect should also be affected by the duration of the stimulus relative w being judged. However, Yarrow and colleagues have demonstrated that the magnitude of such that the chronostasis effect remains constant across a range of target stimulus durations (Yarrow et al 2004). Thus, it does not appear that actions directly affect the internal representation of time itself.…”
Section: First Ifmentioning
confidence: 99%
“…Modulations of the attentional gating of pacemaker outputs to the working memory system or memory processes also have clear predictions regarding timing behavior (Droit-Volet, Clément, & Wearden, 2001;Wearden et al, 1998). More specifically, it has been suggested that more attention paid to time should lead to more pulses being integrated in the clock stage (Zakay & Block, 1995), which in turn code for a longer duration (i.e., dilation of perceived time; Yarrow, Haggard, & Rothwell, 2004). Thus, models such as the STT have consistently proven useful in explaining variations in timing behavior as a result of experimental manipulations.…”
mentioning
confidence: 99%